Wpływ formy finansowania transakcji fuzji i przejęć na wartość rynkową banków komercyjnych w Polsce - Korzeb, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article empirically examines the impact of payment methods on the valuation of commercial banks in the 1994-2006 period. This study describes the advantages and disadvantages of different methods of payment from the perspective of both the buyer and seller. Although most theoretical studies are based on US transactions, the positive stock market response is greater for those transactions in which payment is made in cash in Poland, too. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 138-147